2017
DOI: 10.1371/journal.pone.0178918
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of Alexander Technique lessons or acupuncture sessions for patients with chronic neck pain: A randomized trial (ATLAS)

Abstract: ObjectivesTo assess the cost-effectiveness of acupuncture and usual care, and Alexander Technique lessons and usual care, compared with usual GP care alone for chronic neck pain patients.MethodsAn economic evaluation was undertaken alongside the ATLAS trial, taking both NHS and wider societal viewpoints. Participants were offered up to twelve acupuncture sessions or twenty Alexander lessons (equivalent overall contact time). Costs were in pounds sterling. Effectiveness was measured using the generic EQ-5D to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The assessment of the methodological quality by means of the PEDro scale revealed that, in general, the top 15 most cited clinical trials denoted adequate to good methodological quality, with a final score of six points or higher, except for one study that scored five out of 10 points (Table 1) [36]. Similar findings were observed amongst the 15 most recent articles published in high impact journals (Table 2), although one study denoted poor methodological quality (four out of 10) [37]. One of all studies included achieved excellent methodological quality (10 out of 10) [38].…”
Section: Methodological Quality Of Studiessupporting
confidence: 67%
See 1 more Smart Citation
“…The assessment of the methodological quality by means of the PEDro scale revealed that, in general, the top 15 most cited clinical trials denoted adequate to good methodological quality, with a final score of six points or higher, except for one study that scored five out of 10 points (Table 1) [36]. Similar findings were observed amongst the 15 most recent articles published in high impact journals (Table 2), although one study denoted poor methodological quality (four out of 10) [37]. One of all studies included achieved excellent methodological quality (10 out of 10) [38].…”
Section: Methodological Quality Of Studiessupporting
confidence: 67%
“…Some other visceral sources of NP were enumerated in other clinical trials: (a) hepatitis [37]; (b) systemic disorders, including metabolic disease [30,35,36,41,46,57,58]; (c) abuse of alcohol and drugs [37,54]; (d) rheumatic disease [31][32][33]35,37,46,49,[51][52][53]55,56,58]; (e) cancer [30,31,35,37,42,[51][52][53][55][56][57]; (f) HIV [37]; and (g) infection [30,33,34,40,45,47,57]. Pregnancy was also included as exclusion criteria in almost half of the trials [30,32,34,37,38,40,…”
Section: Eligibility Criteria (Inclusion and Exclusion Criteria) Usedmentioning
confidence: 99%
“…The majority of studies reported the year cost data were collected (Q10), with only 3 studies omitting this level of detail. 19,30,32 The base cost year was also reported for most studies (Q11) with this information not present in only 1 study. 32 Adjustments for costs made in different time periods (Q12) were frequently not necessary due to the majority of studies being run over a 12 month period and therefore not needing to discount for different time periods, with the exception of Barton et al 33 who discounted at a rate of 3.5%.…”
Section: Category 4: Reporting Of Data (Questions 10-12)mentioning
confidence: 99%
“…To date, a set of somatic principles for supporting chronic pain management across a range of conditions has not been theorized or tested, while open structured approaches have been underexplored, and interdisciplinary research on the topic is lacking. 1 There is some research on structured forms such the Alexander Technique (e.g., Essex et al, 2017 ; Woodman et al, 2018 ) and Feldenkrais Method ( Ahmadi et al, 2020 ), while lay books on Hanna somatics for pain exist ( Peterson, 2012 ; St. Pierre, 2015 ). Open somatic frameworks that “rely on more autonomy in movement response lying with the client” ( Weber, 2009 , p. 239) with improvisatory, non-stylized guided sessions (such as Authentic Movement) are missing from research on chronic pain.…”
Section: Introductionmentioning
confidence: 99%